Image Creation Methods in Children's Poetry of the 1990s in Iran - Alireza Emami; Narjes Moghimi (مطالعات زبانی و بلاغی)
Critical study of Iranian children's literature has not yet found its proper place, and it is necessary to critically examine all its constituent elements. In this relation, the 1990s is very important in the history of Iranian children's and adolescent literature from various aspects. For this reason, three hundred pieces of poems of age groups A & B and B& C of the Center for the Intellectual Development of Children and Adolescents, published in the 1990s, were selected for the following research. Then, the techniques of image creation and imagination processing were extracted in these works, in terms frequency. The result of this research indicates that, in the children's poetry of the 90s, the poets have most used repetition, both in form of alliteration and word repetition), followed by proportion, contrast and description. The use of similes is more prevalent than other figures of speech, offering deeper meaning as the age of the targeted audience increases. Personification, synesthesia, and metaphor take the next positions, and poetic etiology has not been practically much used for image creation.